Mutations in HINT1 are one of the most frequent causes of hereditary neuropathy among Czech patients and neuromyotonia is rather an underdiagnosed symptom - Laššuthová, P; Brožková, D Šafka; Krůtová, M; Neupauerová, J; Haberlová, J; Mazanec, R; Dvořáčková, N; Goldenberg, Z; Seeman, P (Neurogenetics, 2015)
Mutations in the HINT1 gene were recently discovered as being the major cause of autosomal recessive axonal neuropathy with neuromyotonia. This combination was clinically recognized and described previously in a few reports but is generally unknown. We aimed to establish the importance of HINT1 mutations as the cause of hereditary neuropathy and particularly hereditary motor neuropathy/axonal Charcot-Marie-Tooth (HMN/CMT2) among Czech patients. Overall, mutations in the HINT1 gene seem to be a surprisingly frequent cause of inherited neuropathy in our group of patients. Biallelic pathogenic mutations were found in 21 patients from 19 families. The prevalent mutation in the Czech population is the p.R37P (95% of pathogenic alleles). Clinically, all patients with biallelic mutations presented with early onset of symptoms at the end of the first decade. Foot/toe extension weakness to plegia was present in almost all patients. Neuromyotonia was present in all but two patients. However, it had been properly recognized in only three patients prior to molecular genetic diagnosis. HINT1 mutations seem to be one of the most frequent causes of inherited neuropathy and are probably the most frequent cause of HMN in Czech patients. We suggest all HMN/CMT2 patients be tested for the presence of the prevalent mutation, the p.R37P.
Keywords: exony; proteiny nervové tkáně; Molecular Diagnostic Techniques; Humans; spinální svalová atrofie; dítě; diagnostické techniky molekulární; Nerve Tissue Proteins; Child; Female; mutace; dospělí; Exons; Genotype; lidé; Charcotova-Marieova-Toothova nemoc; Adult; ženské pohlaví; Male; Adolescent; Charcot-Marie-Tooth Disease; Muscular Atrophy, Spinal; Czech Republic; genotyp; Mutation; Česká republika; mužské pohlaví; mladiství